Potential Interplay between Dietary Saturated Fats and Genetic Variants of the NLRP3 Inflammasome to Modulate Insulin Resistance and Diabetes Risk: Insights from a Meta-Analysis of 19 005 Individuals - Murphy AM (WILEY, 2025)
Scope Insulin resistance (IR) and inflammation are hallmarks of type 2 diabetes (T2D). The nod-like receptor pyrin domain containing-3 (NLRP3) inflammasome is a metabolic sensor activated by saturated fatty acids (SFA) initiating IL-1 beta inflammation and IR. Interactions between SFA intake and NLRP3-related genetic variants may alter T2D risk factors. Methods Meta-analyses of six Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (n = 19 005) tested interactions between SFA and NLRP3-related single-nucleotide polymorphisms (SNPs) and modulation of fasting insulin, fasting glucose, and homeostasis model assessment of insulin resistance. Results SFA interacted with rs12143966, wherein each 1% increase in SFA intake increased insulin by 0.0063 IU mL(-1) (SE +/- 0.002, p = 0.001) per each major (G) allele copy. rs4925663, interacted with SFA (beta +/- SE = -0.0058 +/- 0.002, p = 0.004) to increase insulin by 0.0058 IU mL(-1), per additional copy of the major (C) allele. Both associations are close to the significance threshold (p < 0.0001). rs4925663 causes a missense mutation affecting NLRP3 expression. Conclusion Two NLRP3-related SNPs showed potential interaction with SFA to modulate fasting insulin. Greater dietary SFA intake accentuates T2D risk, which, subject to functional validation, may be further elaborated depending on NLRP3-related genetic variants.